Development of focus controlling method with transcranial focused ultrasound aided by numerical simulation for noninvasive brain therapy. (22nd June 2018) - Kobayashi, Yohei; Azuma, Takashi; Shimizu, Kazuya; Koizumi, Masashi; Oya, Tomomichi; Suzuki, Ryo; Maruyama, Kazuo; Seki, Kazuhiko; Takagi, Shu
Abstract: The use of focused ultrasound for brain therapy has been widely researched. Transcranial focused ultrasound (tFUS) in conjunction with microbubbles has great potential use for blood-brain barrier (BBB) opening and neuromodulation. However, focal aberration due to the skull is a major obstacle to the application of tFUS to brain therapy. A phased array transducer with adaptive differently phased ultrasound waves emitted from each element of the array is widely used to correct distortions due to the skull. In this study, the phase distribution of the array was estimated by the three-dimensional finite differential time domain (FDTD) method using a model based on computed tomography (CT) images. The focal controllability using a 64-channel-array transducer through the skull was examined by both experiments and numerical simulation. The results show that focal aberration was effectively corrected at 500 kHz and 1.7 MHz. Moreover, we demonstrated that the simplest method considering only the time difference of flight is applicable to focal control at low frequencies. It can markedly decrease computational time.